Ajax design patterns - Mahemoff, Michael (O'Reilly Media, 2006)
Ajax, or Asynchronous JavaScript and XML, exploded onto thescene in the spring of 2005 and remains the hottest story among webdevelopers. With its rich combination of technologies, Ajax provides astrong foundation for creating interactive web applications with XML orJSON-based web services by using JavaScript in the browser to processthe web server response. Ajax Design Patterns shows you bestpractices that can dramatically improve your web development projects. It investigates how others have successfully dealt with conflictingdesign principles in the past and then relays.